María Elisa Forero Vivas: dedication and passion for research (REVISTA SAYWA, 2024)
In the section "Personajes UAN", we pay tribute to the outstanding academic career of Professor María Elisa Forero Vivas, a proud native of Bogota with roots in Cundiboyaca. From an early age, Professor María Elisa showed a deep interest in science. Her fascination for this field was awakened during her primary school studies, when she conducted an experiment on the germination of bean, fava bean and pea seeds. She was impressed to witness the germination process and discover that inside each bean was a potential plant. Watching a complete plant emerge from a seed with time, water and air was the starting point of her wonder, curiosity and desire to question, marking the beginning of her journey into the world of science.